Evaluation of intrarenal arterial Doppler spectra in healthy children - Cvitković-Kuzmić, Andrea (Radiology and oncology (Ljubljana), 1999)
Background. The aim of the study was to determine the features of intrarenal arterial Doppler spectra in healthy children by measuring acceleration time (AT) and resistance index (RI). Subjects and methods. RI and AT values were compared between different age groups of children and with normal RI values inadult population. Color duplex Doppler sonography of the intrarenal arteries, using Acuson 128XP10 scanner, was performed in 150 children (300 kidneys), with no clinical or laboratory pathological changes of the urinary tract. All children were classified into three age groups: (1) 52 children between 2 to 6 years of age; (2) 48 children from > 6 to 11 years of age; (3) 50 children from >11 to 16 years of age. Results. The mean RI +/- l. S.D. value in the group I was 0.70 +/- 0.03, in the group 110.625 +/- 0.025 and in the group 1110.585 +/- 0.03. AT ranged from 0.04-0.09 seconds and the mean value of 0.07 +/- 0.01 seconds was the same for all three groups. Conclusions.RI in early childhood is considerably higher as compared to older children and the adult population; after the age of six, RIs become equal to those in the adults. The utilization of RI=0.70, as a threshold value for the increased renal vascular resistance in adults, can be also applied to childrenover 6 years. The detection of renal artery stenosis on the basis of the analysis of acceleration time is the same in children and in adults.
Keywords: Child; Renal artery; Ultrasonography; Ultrasonography, doppler, color